Migration Attributes in Adaptation and Its Correlates during Pandemic: The Socio-ecological Interpretation - Roy, Debdyuti; Acharya, Sankar Kumar; Haque, Monirul; Sarkar, Amrita Kumar; Mandal, Tapan Kumar (Indian Journal of Extension Education, 2022)
Migration is an integral part of social ecology as well as economic development. The four streams of internal migration are rural-rural, rural-urban, urban-rural, and urban-urban. Rural-urban migration has its inherent linkages to agricultural development. In recent years, COVID-19 pandemic has accelerated the process of migration by humongous scale and magnitude. The study was conducted to examine the nature and extent of rural-urban migration, the role, performance and adaptation during migration of family vis-a-vis individual, the inter and intra-level interaction between two sets of variables, and lastly to generate a micro sociological policy based on the empirical research during 2020-21. Three urban and three rural areas of Birbhum district were selected purposively, depending on the prevalence of agricultural and non-agricultural activities. Three hundred respondents were identified through the snowball sampling method. The results show that variables like age, education, family size, income, expenditure, employment and management factor have the highest impact on migration. Also, both the pull and push factors are the main driver of migration.
Keywords: Adaptation; Micro sociological policy; Pandemic; Push factors; Rural urban migration